2021
DOI: 10.1136/emermed-2020-210903
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the utility of Rapid Response EEG in emergency care

Abstract: BackgroundTimely management of non-convulsive status epilepticus (NCSE) is critical to improving patient outcomes. However, NCSE can only be confirmed using electroencephalography (EEG), which is either significantly delayed or entirely unavailable in emergency departments (EDs). We piloted the use of a new bedside EEG device, Rapid Response EEG (Rapid-EEG, Ceribell), in the ED and evaluated its impact on seizure management when used by emergency physicians.MethodsPatients who underwent Rapid-EEG to rule out N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
2
13
1
Order By: Relevance
“…Multiple quality metrics were compared between Rapid‐EEG and a conventional EEG performed immediately afterwards, showing no statistical difference between all metrics except for the power of 60 Hz noise. Wright et al 37 similarly showed that of 38 patients wearing the Ceribell in the ICU, the one patient with NCSE was successfully diagnosed. This study also noted that physicians reported using the Rapid‐EEG contributed to changing clinical management and expedited discharge.…”
Section: Results: 20 Years Of Progress In the Application Of New Noni...mentioning
confidence: 99%
“…Multiple quality metrics were compared between Rapid‐EEG and a conventional EEG performed immediately afterwards, showing no statistical difference between all metrics except for the power of 60 Hz noise. Wright et al 37 similarly showed that of 38 patients wearing the Ceribell in the ICU, the one patient with NCSE was successfully diagnosed. This study also noted that physicians reported using the Rapid‐EEG contributed to changing clinical management and expedited discharge.…”
Section: Results: 20 Years Of Progress In the Application Of New Noni...mentioning
confidence: 99%
“…Time to EEG placement was a median of 5 min with the rapid response system vs. 239 min with conventional EEG (11). Furthermore, this rapid response modality may be economically feasible for both resource limited and rich regions but requires further investigation (35).…”
Section: Technical Aspects Of Eeg Monitoring In the Icumentioning
confidence: 99%
“…In a prospective pilot study of 38 emergency department patients, staff and physicians placed Ceribell® rEEG (RRLM-EEG, rapid response limited montage EEG), and the on-call trained neurologist analyzed the recordings and provided the results [ 4 ••]. One patient was diagnosed with NCSE and received antiseizure medications.…”
Section: Nonconvulsive Status Epilepticusmentioning
confidence: 99%
“…When compared with neurologists, authors reported high sensitivity (100%) and specificity (93%) when evaluating EEG with > 90% seizure burden in status epilepticus. Emergency physicians reported 100% sensitivity and 92% specificity in assessing suspected seizures using the Brain Stethoscope function [ 4 ••]. Sanz-García et al observed a better correlation of the depth of sedation with EEG feature using a machine learning approach than with traditional bispectral index systems in the ICU [ 14 ].…”
Section: Artificial Intelligencementioning
confidence: 99%